2019
DOI: 10.1177/1362361318824103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of memantine in children with autism spectrum disorder: Results from three phase 2 multicenter studies

Abstract: Three phase 2 trials were conducted to assess the efficacy and long-term safety of weight-based memantine extended release (ER) treatment in children with autism spectrum disorder. MEM-MD-91, a 50-week open-label trial, identified memantine extended-release treatment responders for enrollment into MEM-MD-68, a 12-week randomized, double-blind, placebo-controlled withdrawal trial. MEM-MD-69 was an open-label extension trial in which participants from MEM-MD-68, MEM-MD-91, and open-label trial MEM-MD-67 were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…multi-site study in Europe on memantine in ASD and OCD struggled with serious recruitment difficulty was ultimately terminated (Hage et al, 2016;"Translational Adolescent and Childhood Therapeutic Interventions in Compulsive Syndromes (TACTICS)," 2018). A series of 3 large, multi-site studies, one of which was a double-blind placebo-controlled randomized withdrawal trial, and the rest of which were open-label, had mixed results (Hardan et al, 2019). The initial study (MEM-MD-91) was open label and was used to identify memantine responders (as defined by ≥ 10 point reduction in SRS total raw score from baseline at 2 consecutive visits); 517 participants (59.6%) were deemed confirmed responders.…”
Section: Glutamatergic and γ-Aminobutyric Acid (Gaba) Modulating Agentsmentioning
confidence: 99%
“…multi-site study in Europe on memantine in ASD and OCD struggled with serious recruitment difficulty was ultimately terminated (Hage et al, 2016;"Translational Adolescent and Childhood Therapeutic Interventions in Compulsive Syndromes (TACTICS)," 2018). A series of 3 large, multi-site studies, one of which was a double-blind placebo-controlled randomized withdrawal trial, and the rest of which were open-label, had mixed results (Hardan et al, 2019). The initial study (MEM-MD-91) was open label and was used to identify memantine responders (as defined by ≥ 10 point reduction in SRS total raw score from baseline at 2 consecutive visits); 517 participants (59.6%) were deemed confirmed responders.…”
Section: Glutamatergic and γ-Aminobutyric Acid (Gaba) Modulating Agentsmentioning
confidence: 99%
“…Interestingly, there was a non-significant improvement in social responsiveness as assessed by parents (7.8 points, effect size = 0.52) which is a medium effect size. While a minimal clinically important difference (MCID) for the SRS in children with autism has not been determined in children with ASD, some authors have suggested using a change in the SRS of > 10 to indicate a MCID and to address the concern that smaller changes may be within the range of a placebo effect (Hardan et al 2019). The non-significant change of .8 points observed in this study is below this proposed MCID threshold but still a signal of a large enough change to warrant further investigation in larger, placebo-controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Memantine and placebo were initiated at 3 mg and the dose was titrated up by 3 mg a week to a maximum of dose of 6, 9, or 12 mg depending on weight and tolerability with dose adjustments conducted between biweekly study visits as needed. Maximum daily doses per weight classes are as follows: 20-40 kg (6 mg), 40-60 kg (9 mg), and >60 kg (12 mg) and were informed by FDA submissions from Forest Pharmaceuticals for trials of memantine ER (Aman et al 2017; Hardan et al 2019). In the Forest Pharmaceuticals trial, the maximum dose for the highest weight category was 3 mg higher than this evaluation of neurocognitive outcomes.…”
Section: Designmentioning
confidence: 99%
“…Another report from the same investigative group reported on a series of trials of memantine ER in ASD: (1) a 50-week open-label, lead-in trial to identify responders; (2) a 12-week randomized, double-blind, placebo-controlled RCT; and (3) <48-week openlabel extension to the double-blind RCT that was discontinued early (Hardan et al 2019). Together, the studies enrolled 906 verbal children with ASD across 118 sites worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation